Optimization of spiritual resilience, self-motivation, and life skills of Lowokwaru Assisted Residents through self-aware training - Mustiningsih, Mustiningsih; Benty, Djum Djum Noor; Argadinata, Hasan (2023)
The program to increase spiritual resilience, self-motivation, and life skills for male-assisted residents at the Lowokwaru Correctional Institution in Malang City, community service aims to achieve several goals that cover important aspects of their development. To achieve this goal, various methods are used, such as lectures, discussions, ice breaking, and training in skills to process old tires into souvenirs that have economic value. While the results of the activity are indirectly concluded (a) the implementation of the training generally has a positive effect on increasing participant motivation during or after the training activity, (b) students are pleased with the speaker's presentation during the training, and (c) participants are still eager to follow up on the training's outcomes, as evidenced by their enthusiasm to plan similar training.